Network-Based Organizations in the Extended Enterprise Era: The Case of the After-Sales Services Network Configuration and IT-Acceptance - Taifi, Nouha (International Journal of Economics, Business and Management Studies, 2022)
The extended enterprise has various types of partners in its supply and value chain. It is important to continuously define its strategic dynamisms and mechanisms related to its external environment in which there are inter-organizational collaborations with the partners. The paper questions the evolution and development of a specific type of partners that are the network of after-sales services that continuously indeed knows sustainable development. The after-sales services are services provided to customers after-sales of the products as repair solutions, revisions of spare parts for the customer satisfaction. The results of the study argues about the type of ties among the extended enterprise and these partners presenting quantitative data about different types of managerial dynamisms in an automotive context. The paper also discusses the continuous development of this network in terms of strong and weak ties presenting some theoretical propositions that need to be further developed with respect to co-evolution of the organizations in the network and the extended enterprise.